Menstrual Abnormality Experienced in Well Differentiated Thyroid Carcinoma Female Patients After Single Dose Radioiodine Therapy – Mono Institute Based Experience - Sharmin, Samira; Billah, Syed Muhammad Baqui; Rahman, Hosne Ara; Naznin, Afroza; Yasmin, Farida; Uddin, Md Monir (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Menstruation is a natural event in all women between puberty and menopause. Radioiodine therapy is the popular method of treatment in Differentiated Thyroid Carcinoma (DTC) worldwide. Considering these two, this study was designed to evaluate the experience of menstrual problems of DTC patients after a single dose of Patients and radioiodine therapy Patients and Methods: and This retrospective observational study conducted at INMAS, Mitford, Dhaka, analyzed data obtained between January 2020 and December 2023 from 79 female patients with DTC who were referred for radioiodine therapy for their clinical state(s), about 75mci (2.7GBq). Results: Of the 79 female patients, 12 (15.1%) reported no problem or menstrual abnormality, transient amenorrhea was noticed among 16 (20.6%), oligomenorrhea identified in 12 (15.1%), hypomenorrhea in 13(16.5%), delayed pregnancy in 1 (1.2%), no problem with pregnancy reported by 2 (2.5%), and persistent problem with menstruation before and after therapy was reported by 11 (13.9%) patients after receiving radioiodine therapy. Menopause was reported by 12 (15.1%) during the study period. In this study, mean age of the study subjects were 30.7±5.01 years. Conclusion: This study reveals that female patients receiving radioiodine therapy had experienced menstrual abnormalities of varying degrees. Bangladesh J. Nuclear Med. 27(2): 213-216, 2024